Immunomodulatory and anti-inflammatory effects of bioactive compounds of Cassia angustifolia Vahl. leaf extract - Abood, Walaa Najm (Plant Science Today, 2024)
Cassia angustifolia Vahl. is a medicinal plant known for its efficacy in treating various, including respiratory conditions and skin inflammation. It possesses antibacterial and anticancer properties. This work investigated the immunomodulatory and anti-inflammatory effects of C. angustifolia. The ethanol leaf extract of C. angustifolia was utilized to examine gene expression related to angiogenesis cytokines in RAW 264.7 macrophage cells. The results demonstrated a significant increase in the viability of treated macrophage RAW 264.7 cells, accompanied by an improvement in angiogenesis cytokines expression and a dose-dependent inhibition of nitric oxide production. GC-MS analysis identified 11 active components within the extract, each exhibiting distinct biological activities such as antioxidant, antitumor and anti-inflammatory effects. Notable compounds include hexadecanoic acid, 2-pentadecanone, phthalic acid, oxalic acid, carbonic acid, tricosane, undecanal and many others. In conclusion, ethanol leaf extract of C. angustifolia exhibits immunomodulatory and anti-inflammatory effects by inhibiting nitric oxide production and enhancing the expression of angiogenesis cytokines.